2017
DOI: 10.1007/s00464-017-5517-x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cholecystostomy: prognostic factors and comparison to cholecystectomy

Abstract: Background Data regarding long-term outcomes following percutaneous cholecystostomy (PC) are limited, and comparisons to cholecystectomy (CCY) are lacking. We hypothesized that chronic disease burden would predict 1-year mortality following PC, and that outcomes following PC and CCY would be similar when controlling for preprocedural risk factors. Methods We performed a 10-year retrospective cohort analysis of patients with acute cholecystitis managed by PC (n = 114) or CCY (n = 234). Treatment response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(28 reference statements)
0
10
1
Order By: Relevance
“…PC as a bridge to cholecystectomy or as a definitive treatment has been increasingly used as an alternative initial treatment option for patients with AC. However, 60-70% of patients with AC do not undergo interval cholecystectomy after PC [15][16][17][18]. In our study, 67 (32.7%) patients did not undergo interval cholecystectomy after PC, which is considerably lower than that in previous studies [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 69%
“…PC as a bridge to cholecystectomy or as a definitive treatment has been increasingly used as an alternative initial treatment option for patients with AC. However, 60-70% of patients with AC do not undergo interval cholecystectomy after PC [15][16][17][18]. In our study, 67 (32.7%) patients did not undergo interval cholecystectomy after PC, which is considerably lower than that in previous studies [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 69%
“…The incidence of mortality was demonstrated by 17 studies [ 14 23 , 25 27 , 29 – 31 , 33 ]. The utilisation of percutaneous cholecystostomy was associated with a significant increase in mortality (POR = 4.85; 95% CI: 1.02–7.30; p = 0.0001) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Chou et al revealed that performing early PC (<24 h) when AC is identified may benefit patients by shortening the hospital stay and reducing the incidence of procedure-related bleeding (30). Bickel et al also revealed that patients with early PC insertion (<2 days) had a significantly lower incidence of conversing to open cholecystectomy followed by LC than those with late PC insertion (3-6 days) (34). Both Noh et al and Viste et al revealed significant decreases in white blood cell (WBC) and C-reactive protein (CRP) levels after PC; notably, the latter study mainly focused on patients with acute acalculous cholecystitis (32,33).…”
Section: Efficacy Of Percutaneous Cholecystostomymentioning
confidence: 99%